The gut microbiome: A line of defense against tuberculosis development - Yu, Ziqi; Shen, Xiang; Wang, Aiyao; Hu, Chong; Chen, Jianyong (Frontiers in Cellular and Infection Microbiology, 2023)
The tuberculosis (TB) burden remains a significant global public health concern, especially in less developed countries. While pulmonary tuberculosis (PTB) is the most common form of the disease, extrapulmonary tuberculosis, particularly intestinal TB (ITB), which is mostly secondary to PTB, is also a significant issue. With the development of sequencing technologies, recent studies have investigated the potential role of the gut microbiome in TB development. In this review, we summarized studies investigating the gut microbiome in both PTB and ITB patients (secondary to PTB) compared with healthy controls. Both PTB and ITB patients show reduced gut microbiome diversity characterized by reduced Firmicutes and elevated opportunistic pathogens colonization; Bacteroides and Prevotella were reported with opposite alteration in PTB and ITB patients. The alteration reported in TB patients may lead to a disequilibrium in metabolites such as short-chain fatty acid (SCFA) production, which may recast the lung microbiome and immunity via the “gut-lung axis”. These findings may also shed light on the colonization of Mycobacterium tuberculosis in the gastrointestinal tract and the development of ITB in PTB patients. The findings highlight the crucial role of the gut microbiome in TB, particularly in ITB development, and suggest that probiotics and postbiotics might be useful supplements in shaping a balanced gut microbiome during TB treatment.